2018
DOI: 10.1186/s13017-018-0193-2
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic colitis caused increased early and delayed mortality

Abstract: BackgroundIschemic colitis remains a challenge for the surgeon, both in its diagnosis and treatment. Data from a single tertiary center, of patients diagnosed with ischemic colitis, was collected. An attempt was made to delineate the patients requiring surgical intervention.MethodsA retrospective study was undertaken in patients diagnosed with ischemic colitis admitted to Rambam Health Care Campus between 2011 and 2016. The primary outcome was defined as mortality. Secondary outcomes were defined as complicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…The mortality rate was 11% in the study by Brandt et al [22] In another study, a mortality rate of around 29% was found. [25] In these studies, it was shown that mortality is significantly increased especially with right colon or pancolonic involvement. The main reason for such obvious differences between studies is the difference in the patients included.…”
Section: Discussionmentioning
confidence: 97%
“…The mortality rate was 11% in the study by Brandt et al [22] In another study, a mortality rate of around 29% was found. [25] In these studies, it was shown that mortality is significantly increased especially with right colon or pancolonic involvement. The main reason for such obvious differences between studies is the difference in the patients included.…”
Section: Discussionmentioning
confidence: 97%
“…AMI is caused by a sudden interruption of the blood supply for a segment of the small intestine, causing ischemia, cellular damage and intestinal necrosis. In a recently published article, Gilshtein et al identified 63 patients with ischemic colitis, the most common form of AMI, in one tertiary center 11 . Most patients were treated clinically, and only the 20% most serious cases, with complications such as peritonitis, hemodynamic instability and untreatable disease, received surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In a recently published article, Gilshtein et al identified 63 patients with ischemic colitis, the most common form of AMI, in one tertiary center 11 . Most patients were treated clinically, and only the 20% most serious cases, with complications such as peritonitis, hemodynamic instability and untreatable disease, received surgical intervention.…”
Section: Discussionmentioning
confidence: 99%